(3GdeONd Edi CSS Yde GdEbJUGOs - (3GSeGYjd(B, (3eMeO GdgGTes ((3GdGScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2005)
(3Yde GdGbJUGO hehVhY GdOQGSGJ GdGbJUGOjI(B: (3Yde GdGbJUGO, GdeTcdI GdGbJUGOjI, WHjYI hhXGFa GdfXGe GdGbJUGOj, GdShb, GdbjeI(B: (3fXQjI GdbjeI, JMdjd GdefaYI, efMfjGJ GdShGA, GdWdH, GdYQV, GdWdH hGdYQV hJMdjd Kef GdSdYI, GdGfJGL(B: (3GdGfJGL, GdYdGbI Hjf GdeSJNOe hGdefJL, efMfjGJ GdGjQGO, GdJcGdja, JhGRf GdeDSSI aj Xd GdefGaSI GdcGedI, CShGb GdefGaSI ZjQ GdcGedI, GdefGaSI GdGMJcGQjI, GdGMJcGQ, GdJejjR GdGMJcGQj, efGaSI GdbdI, JONd GdMcheI aj JMOjO GdCKeGf, GdJhRjY(B: (3fXQjI GdJhRjY, fXQjI GdGfJGLjI GdMOjI, GdCLhQ, GdQjY, GdaGFOI, GdQHM, GdCKeGf aj GdGbJUGO GdGTJQGcj, GdONd Gdbhej hGdJfejI hGdJNWjW hGdScGf(B: (3GdONd Gdbhej, GdJfejI hGdJNWjW GdGbJUGOj, GdScGf(B.s
(3GdeQGLY U(B.586s
Keywords: (3GdJNWjW GdGbJUGOjs; (3GdJfejI GdGbJUGOjIs; (3Yde GdEbJUGOs